Impact of Advanced Maternal Age on Perinatal Outcomes - İnegöl Gümüş, İlknur and Kamalak, Zeynep and Yuvacı, Hilal and İltemur Duvan, Candan and Öztürk Turhan, Nilgün (Gynecology Obstetrics & Reproductive Medicine, 2008)
OBJECTIVES: To investigate the impact of advanced maternal age on perinatal outcomes. STUDY DESIGN: In this retrospective study, pregnancy records of 616 singletons were reviewed. Subjects were divided into 3 age groups: Group 1; 20-29 years (n=386), Group 2; 30-39 years (n=171) and Group 3; 40 years and older (n=59). The groups were compared for maternal datas such as parity, pre and post-pregnancy body mass index and for obstetrics complications. RESULTS: Pre and post-pregnancy body mass index, gestational diabetes mellitus, delivery <37 weeks, prevalance of cesarean section and proportion of babies admitted to neonatal intensive care unite were significantly higher in women above 40 years (p<0.05). Pregnants aged 40 and older had low birth weight babies than others (3270.8±612.06 gr, p=0.037). CONCLUSIONS: Increasing maternal age showed a significant increase in gestational diabetes melllitus and excess rate of cesarean section. Despite the increased risk of complications in women above 40 years they should have healthy babies by counselling for care in a specialised centre.